Experimental IR meets multilinguality, multimodality, and interaction : 7th International Conference of the CLEF Association, CLEF 2016, Évora, Portugal, September 5-8, 2016, Proceedings /: 7th International Conference of the CLEF Association, CLEF 2016, Évora, Portugal, September 5-8, 2016, Proceedings. (2016) - Unknown
No abstract available